Pengaruh Transportasi, Infrastruktur Jalan, dan Ketersediaan Informasi terhadap Kepuasan Pengunjung Candi Mendut - Putra, Archie Zakkharia Dakarwan; Yasmine, Natasya Veronika; Maharani, Ulfa Ayu; Muzaki, Muhamad Thoriq; Sinaga, Karel Tua Partogi; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2026)
Visitor satisfaction is a key indicator in assessing the success of managing heritage tourism destinations with high historical and cultural value. The suboptimal accessibility and availability of information in the Mendut Temple area present issues that require in-depth analysis. This study aims to determine the influence of transportation accessibility, road infrastructure, and information availability on visitor satisfaction at Mendut Temple. The study employs a quantitative approach using a survey method involving 148 Mendut Temple visitors selected via purposive sampling and distributed through social media, followed by analysis using multiple linear regression with the assistance of SPSS software. The results indicate that, when considered individually, ease of transportation access does not significantly influence visitor satisfaction because the majority of visitors come from areas geographically close to the tourist site, so transportation is not a primary consideration in their travel experience. Meanwhile, road infrastructure and information availability each have a positive and significant effect on visitor satisfaction, with information availability being the most dominant variable. Simultaneously, the three variables together explain 67.7% of the variation in visitor satisfaction at Mendut Temple. This study reinforces the empirical basis that the availability of information is the most critical dimension of accessibility in shaping visitor satisfaction at cultural heritage-based tourist destinations. Practically, this study recommends that the managers of Mendut Temple and the Magelang Regency government prioritize the enhancement of digital tourism information, informative signage, and the continuous improvement of road infrastructure to create a more comfortable and satisfying visitor experience, thereby encouraging repeat visits to Mendut Temple.